Mycobiota from Cyclamen persicum and its interaction with Botrytis cinerea - Rivera, Marta Carolina (2009)
Sixty-six fungi isolated from cyclamen phylloplanes were identified and assessed in vitro for antagonism to B. cinerea on leaves, petals, petioles and peduncles. The estimation of pathogen conidial production was used as indicator of biocontrol ability of each of the strains. They were classified by cluster analysis resulting in four categories according to their behavior in the different organs. The most promising category included 34 isolates that significantly reduced pathogen inoculum in all the organs. Correspondence analysis showed association among leaf isolations, strains of Clonostachys rosea and Penicillium spp. and the best biocontrol performance. The statistical analysis was successful in dealing with this complex set of experimental data. Leaf fungal diversity was higher than those of petals and petiols, with Shannon values of 2.7, 0.9 and 0.5 respectively. Evidence for antibiosis and hyperparasitism was found for C. rosea.